Leaning-teaching process based on breast cancer control activities in communitary context of participation: report experience - Escolástica Rejane Ferreira Moura; Raimunda Magalhães da Silva (Rev Rene)
Report a leaning-teaching experience process. The objective was to analyze the leaning-teaching process based on breast cancer control activities and evaluation the lack of knowledge of the team. It was descritive study where they appied three steps from Saul (1988). Was developed – describing reality; reality criticism and collective creation. It was evaluation that the leaning-teaching process improve group participation by considering the own reality as hallmark of discussions. The participants presented knowledge lack in management, technical practices, difficult of dealing with local culture values as well.